Climate Change Mitigation Policies: Implications for Agriculture and Water Resources. (August 2013) - Frisvold, George B.; Konyar, Kazim
Abstract This study examines how the proposed American Clean Energy and Security Act (H.R. 2454) would affect U.S. agriculture with special reference to water resources. The bill's cap and trade provisions for greenhouse gases would significantly raise fertilizer, irrigation pumping, and other energy‐related costs. By 2030, it would reduce U.S. irrigation water use by >11 percent and fertilizer use by >18 percent with positive implications for water conservation and quality. Carbon offset provisions create financial incentives for farmers to sequester carbon by planting trees on cropland, reducing agricultural production and raising prices. Because sequestration potential differs by region, most of the estimated 51 million acres of converted cropland would be in the Corn Belt and Mississippi Delta. Afforestation would reduce Delta water use further, but increase water use in other regions compared to cap and trade alone. Compared to a no‐policy baseline, irrigation water use declines 10 percent nationally, but increases in the Southern Plains. H.R. 2454 may have significant water conservation effects in some regions, but increase competition for water in others. By reducing fertilizer use and dramatically altering land use patterns in parts of the Mississippi Basin, it may also provide unexpected water quality benefits. Unintended water use and quality consequences of climate policies merit further research.